Spinal posture, stiffness and motor control during pushing and pulling in flexion and active extension patterns of chronic nonspecific low back pain - Geoffrey C. W. Yu; Jessica C. Y. Yeung; Matthew H. M. Chan; Kate C. T. Tong; Sara K. W. Poon; Eliza R. Sun; Sharon M. H. Tsang (Scientific Reports)
Abstract This cross-sectional study aimed to compare the change in spinal posture, mechanical stiffness, and motor control of the thoracolumbar spine in individuals who were asymptomatic and those with chronic nonspecific low back pain (LBP) of flexion pattern (FP) or active extension pattern (AEP) during pushing and pulling tasks performed in standing. The real-time thoracolumbar posture, mechanical stiffness, electromyographic amplitude and synergy between specified trunk muscle pairs (Internal Oblique and Multifidus, Rectus Abdominis and Erector Spinae, Internal Oblique and Rectus Abdominis, Multifidus and Erector Spinae) were analysed during quiet standing, standing pushing and pulling tasks against a load standardized at 15% of the individual body weight in a total of 39 individuals (asymptomatic, n = 14; FP, n = 11; AEP, n = 14). Pulling task resulted in greater lumbar posterior translation (p = 0.009) and Rectus Abdominis activity (p = 0.006), but smaller lumbar lordosis (p < 0.001) when compared to pushing task. Pulling task also resulted smaller lumbar lordosis (p < 0.001) and thoracic kyphosis (p = 0.003) comparing to upright standing. AEP group showed a significantly greater amplitude of their Internal Oblique activity when compared to those who were asymptomatic across all tasks (p = 0.001). Findings suggested that pulling manoeuvre in standing produced greater shear at the lumbar spine than that of pushing manoeuvre. Individuals with low back pain executed the low-load push/pull tasks with the motor strategy largely comparable to asymptomatic group. Future studies investigating the cumulative effect of repetitive push/pull loadings on the movement and motor control of the spine are warranted to better understand the long-term impacts on spinal health.